KURIKULUM DAN PEMBELAJARAN PESANTREN TIPOLOGI CAMPURAN (STUDI PADA PESANTREN PERSIS 110 MANBA’UL HUDA KOTA BANDUNG) - Huda, Miftahul (Dirasa Islamiyya: Journal of Islamic Studies, 2024)
This research focuses on examining the curriculum and teaching of a mixed typology pesantren at Persatuan Islam (Persis) 110 Manba'ul Huda. The method used in this research is a descriptive qualitative method with a field research approach. This type of research describes systematically and factually the events or situations concerning the phenomenon being studied. The results of this study conclude that Persatuan Islam (Persis) 110 Manba'ul Huda in Bandung is an educational institution that adopts both khalafi (modern) and salafi (traditional) pesantren models, making it a mixed typology pesantren. The curriculum and teaching structure of the pesantren that adopts the khalafi model is implemented by integrating the pesantren curriculum with the Ministry of Religious Affairs curriculum. Meanwhile, the curriculum and teaching structure that adopts the salafi pesantren model is implemented by opening the Salafiah Pesantren Persatuan Islam Manba'ul Huda program, which includes studying classical Islamic texts (yellow books) using traditional teaching methods such as memorization and translating texts during the learning process.